Perbedaan Kualitas pada Remaja Overweight dan Non-Overweight di SMA Negeri 10 Kota Jambi - Fatimah, Annisa; Wulansari, Arnati; Rahmawati, Helfi; Fatmawati, Tina Yuli (3031-8572, 2024)
e level of food consumption in the adolescent age group is still classified as less in accordance with balanced dietary guidelines, which is still in the low category in the consumption of protein, fruits and vegetables, and the consumption of fat, sugar and salt is quite high. However, if calorie intake is not balanced with the amount of energy expended through physical activity, an increase in energy reserves stored in adipose tissue can lead to overweight. Diet quality, as an assessment of adherence to a balanced diet, has a role to play in improving health by recommending dietary diversity to meet nutrient needs and by preventing food-related noncommunicable diseases. The aim of this study was to determine the difference in diet quality between overweight and non-overweight adolescents in SMA N 10 Jambi City. This research was conducted in May-July 2024 in SMA N 10 Jambi City. This research is a quantitative study with cross sectional design. Data was collected using 3x24 hour food recall interviews. The sample size was 85 adolescents. Data analysis in this study used univariate and bivariate analysis using T- test. The results showed a percentage description of diet quality in adolescents, namely as many as 85 people (100%) had poor diet quality and as many as 41 people (48.2%) had overweight nutritional status. There is no difference between the diet quality of overweight adolescents and non-overweight adolescents with a Sig. 0,284. It can be concluded that there is no difference between the dietary quality of overweight and non- overweight adolescents. It is recommended that schools, in collaboration with the health centre, carry out counselling on the consumption of balanced, nutritious food, guided by the contents of my plate, in order to improve the quality of adolescent diet.